No simple explanation for Kenyan's dominance -- Running - Phillips, E. (http://www.utsandiego.com/, 1992)
Excerpt of examinations of the Swedish exercise physiologist Bengt Saltin, who went to Kenya last year and conducted some running research of his own to answer the question: Why do Kenyans win such a lot of races? What he found was that, predictably, there is no simple reason why Kenyans as a people tend to be superior distance runners. There are some traditional explanations.